2020
DOI: 10.3390/microorganisms8111824
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus: How Its Lytic Phase Contributes to Oncogenesis

Abstract: Epstein–Barr Virus (EBV) contributes to the development of lymphoid and epithelial malignancies. While EBV’s latent phase is more commonly associated with EBV-associated malignancies, there is increasing evidence that EBV’s lytic phase plays a role in EBV-mediated oncogenesis. The lytic phase contributes to oncogenesis primarily in two ways: (1) the production of infectious particles to infect more cells, and (2) the regulation of cellular oncogenic pathways, both cell autonomously and non-cell autonomously. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 104 publications
(146 reference statements)
1
71
0
Order By: Relevance
“…EBV can transform primary B cells into lymphoblastoid cell lines in vitro and may cause post-transplantation lymphoproliferative disease (PTLD). Increasing evidence indicates that lytic phase gene expression also contributes to EBV oncogenesis [ 23 ].…”
Section: Overview Of Ebv Lytic Replicationmentioning
confidence: 99%
“…EBV can transform primary B cells into lymphoblastoid cell lines in vitro and may cause post-transplantation lymphoproliferative disease (PTLD). Increasing evidence indicates that lytic phase gene expression also contributes to EBV oncogenesis [ 23 ].…”
Section: Overview Of Ebv Lytic Replicationmentioning
confidence: 99%
“…Indeed, the reasons for EBV’s ability to differentially reactivate under different conditions has been a long-standing question with relevance also to several diseases, including transplant- and other immunosuppression-related lymphoproliferative diseases and lymphomas. On the one hand, with the lytic phase playing an essential role in development of lymphoid and epithelial EBV cancers [ 3 , 4 ], such tumors could be prevented by blocking lytic activation. On the other, shifting the balance towards the lytic phase, thereby eliminating the residual subpopulation of the refractory cells, would be a tremendous boost to oncolytic therapies in which latently infected malignant cells are targeted for killing by induction of the viral lytic phase.…”
Section: A Two-population Problemmentioning
confidence: 99%
“…It establishes lytic infection in epithelial cells and B lymphocytes, but the predominant mode of infection is the latency in B lymphocytes. The EBV latent infection is a common cause for B cell malignancy, whereas abortive lytic infections are also associated with the EBV-related oncogenesis [ 149 , 150 ]. Tsai et al showed that in primary B lymphocytes, EBV DNA was localized next to the ND10 components, Daxx and ATRX [ 151 ], which may reflect the host attempt to silence the incoming genome.…”
Section: Dual Role Of Nd10 In γ-Herpesvirus Infectionmentioning
confidence: 99%